TECHNOLOGY OF TEACHING FOREIGN LANGUAGES ON THE BASIS OF WEB APPLICATIONS - Kurbanova Sabohat Rahmonovna (International Journal of Human Computing Studies, 2020)
What is the best way to learn a new language? Ask anyone who speaks more than one language so you get a comprehensive answer. Classes, textbooks, language exchange programs are tools that help you learn a language to a certain extent. Language learning apps are another tool that is becoming increasingly popular. However, each program has its own direction and method of teaching.